Project-based learning as a facilitator to promote students' technology competencies - Bagheri, Mohsen; Wan Ali, Wan Zah; Abdullah, Maria Chong; Mohd Daud, Shaffe (Academic World Education & Research Center, 2013)
Due to the close relationship between educational technology as a field of study on the one hand and technological progress as a fact on the other, the very nature of this field has undergone tremendous shift which has resulted in a transmogrification, changes which are evinced by the roles of educational technologist. Therefore, not only should educational technology training centers aim at transferring concepts related to this major to learners, but they should also focus on developing basic skills that students need, such as technological competencies. This article sought to examine the effects of project-based learning strategy (PoBL) on students’ technology competency in a system-based education course offered in the educational technology department of Arak University in Iran. In order to achieve this end, a sample of 78 students majoring in the field of educational technology who enrolled in the system-based education course was selected. Subjects were randomly assigned to one of two groups: the experimental group (PoBL strategy) and the control group (conventional teaching strategy). The educational course involved 12 sessions over the course of one semester of the 2011-2012 academic year, with each session lasting approximately 90 minutes. The technology competency questionnaire was administrated three times (i.e. pretest, post-test one, and post-test two), while the experimental group received the PoBL strategy and the control group was exposed to conventional teaching (CT) methods. The results of two way repeated measure ANOVA revealed that students who were taught using Poll strategy performed better in terms of technology competency compared to students who were taught using CT strategy.